2012
DOI: 10.5539/jas.v4n2p31
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozonated Water on Storage Life and Postharvest Quality of Iranian Table Grape (cv. Bidaneh Qermez)

Abstract: Grape as a perishable fruit is susceptible to fungal infection especially Botrytis cinerea, as an agent of gray mold, and berry dehydration. There are limitations in use of synthetic chemical compounds to control postharvest losses in grape and other fruits. The aim of this study was the evaluation of non-chemical and safe methods for this purpose. Therefore, ozone soluted at 0.3 ppm concentration with three treatment times (5, 10 and 15 min), in water was applied on 'Bidaneh Qermez' grape cultivar. Qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…It might be because of lower water loss, the slower rate of respiration and ethylene evolution as a consequence, the conversion of sucrose into glucose and fructose might have been delayed. Our results are in agreement with Cayuela et al 2010 [8] and Geransayeh et al 2012 [15] who reported increase in TSS in ozone treatment throughout storage. On the contrary, in the majority of available literatures, it is reported that significant differences in total soluble solids content between ozonated and untreated samples was not noticed.…”
Section: Total Soluble Solids (°Brix)supporting
confidence: 93%
See 1 more Smart Citation
“…It might be because of lower water loss, the slower rate of respiration and ethylene evolution as a consequence, the conversion of sucrose into glucose and fructose might have been delayed. Our results are in agreement with Cayuela et al 2010 [8] and Geransayeh et al 2012 [15] who reported increase in TSS in ozone treatment throughout storage. On the contrary, in the majority of available literatures, it is reported that significant differences in total soluble solids content between ozonated and untreated samples was not noticed.…”
Section: Total Soluble Solids (°Brix)supporting
confidence: 93%
“…The positive effect of treatments might be assigned to decrease in rate of respiration and other physiological activity as a result of inactivation of enzymes by oxidation. Our findings are in corollary with authors like Geransayeh et al (2012) [15] and Artes-Hernandez et al (2003) [5] who reported ozone treatment decreased the weight loss of grapes samples noticeably. Glowacz et al (2015b) observed similar results in red bell peppers, but without any significant effect on weight loss, texture, and fruit colour.…”
Section: Physiological Loss In Weight (Plw)supporting
confidence: 92%
“…The use of ozone at low doses in the treatment of fruits, contributed to the maintenance of appearance at acceptable levels (Geransayeh, Mostofi, Abdossi, & Nejatian, 2012;Sarig et al, 1996).…”
Section: Sensory Analysismentioning
confidence: 99%
“…The surface treatment of fruits with various synthetic chemicals is a good strategy for inhibiting the growth of microorganisms in order to improve the shelf life of fresh and fresh-cut fruits (Geransayeh et al, 2012). The antimicrobial action of organic acids was attributed to pH reduction, disturbance of membrane transport and/or permeability, anion accumulation, inhibition of enzymes, cytoplasm acidification (Parish et al, 2003), as well as to the specific antimicrobial effect of particular anionic species (Ramos-Villarroel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%